2003
DOI: 10.1016/s0378-7788(02)00142-1
|View full text |Cite
|
Sign up to set email alerts
|

Energy performance of daylight-linked automatic lighting control systems in large atrium spaces: report on two field-monitored case studies

Abstract: This paper presents the field-measured energy performance of two common types of daylight-linked lighting control systems, continuous dimming and automatic on/off installed in two existing large atrium spaces located in Canada. The daylighting performance was evaluated based on the daylight contribution to the indoor illuminance and the amount of electrical lighting displaced by daylighting via the daylight-linked lighting control systems. Measured daylighting contribution to the space indicates that significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(21 citation statements)
references
References 1 publication
1
20
0
Order By: Relevance
“…On/off and continuous dimming controls are two commonly used daylight linked control systems. Previous studies showed that both of the control systems can reduce electrical lighting energy consumption significantly in the buildings that have indoor daylight access [45][46][47][48][49][50][51]. However, the on/off control system requires extra attention to adequate zoning and its calibration (based on space daylight availability) [46].…”
Section: Lighting Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…On/off and continuous dimming controls are two commonly used daylight linked control systems. Previous studies showed that both of the control systems can reduce electrical lighting energy consumption significantly in the buildings that have indoor daylight access [45][46][47][48][49][50][51]. However, the on/off control system requires extra attention to adequate zoning and its calibration (based on space daylight availability) [46].…”
Section: Lighting Controlmentioning
confidence: 99%
“…Previous studies showed that both of the control systems can reduce electrical lighting energy consumption significantly in the buildings that have indoor daylight access [45][46][47][48][49][50][51]. However, the on/off control system requires extra attention to adequate zoning and its calibration (based on space daylight availability) [46]. Moreover, a frequent variation in the daylight levels (due to unstable weather conditions) around the switching illuminance creates a condition of rapid and frequent switching of lights on and off in the on/off lighting control system that disturbs occupants and reduces the lamp life [52].…”
Section: Lighting Controlmentioning
confidence: 99%
“…Although there have been several studies investigating energy effi ciency in lighting design in buildings, many of these studies are focusing on offi ce buildings or commercial buildings other than spa buildings (see, for instance, Santamouris et al , 1994 ;Fu Min et al , 1997 ;Kim and Mistrick, 2001 ;Li and Lam, 2001 ;Atif and Galasiu, 2003 ). There is hardly any study that investigates energy-effi cient lighting in an exclusive spa project.…”
Section: The Present Study and Its Originalitymentioning
confidence: 99%
“…Several research studies (measurement studies [4,7,8] and simulation analyses [9][10][11][12][13][14]) have shown that by applying proper daylight controllers, up to 60% of lighting energy could be saved. However, these studies have not been able to encourage designers and engineers to apply these kinds of daylighting controllers in their projects, [15].…”
Section: Introductionmentioning
confidence: 99%